Macauley's thumb - Williford, Lex, 1954- (Iowa short fiction award., 1994)
A husband and wife, unable to speak to each other without arguing, face the dissolution of their marriage when they smuggle his mother's body out of Mexico. Two boys, confronting abandonment by their father, go to the Texas State Fair and stumble upon a way to get their mother out of bed. Thomas "Hoot" Ponder and his nephew find common ground in whiskey and storytelling amid the comedy surrounding death and dying. A chiropractor who loves science fiction movies struggles with his sexual fantasies about one of his patients, a Wal-Mart cashier who can't stop talking about her pain. In the powerful title story, Cal Macauley--driven mad by his wife's horrible death--faces mourning, regret, and the inevitability of forgetting by striking out against himself and the rattlesnakes on his mountain.